Energy Approach to Measure the Region’s Assimilative Capacity - Belik, I.S.; Starodubets, Natalya Vladimirovna; Yachmeneva, Alena Igorevna (Economy of Regions, 2017)
One of the important problems of the environmental economics is the development of methodology for quantifying the assimilative capacity (AC) of a territory. The article analyzes the existing approaches to determining and assessing the AC of a territory. We justify the advantages of using the energy approach. We authors’ method consists in using the maximum permissible energy load (MPEL) for quantitative assessment of the AC of a territory. MPEL is a value that the ecological and economic system can withstand for a long time without changing its properties. We determine MPEL on the basis of data on the ability of various categories of land to absorb greenhouse gases (GHG), as well as the specific GHG emissions per ton of conventional fuel. Further, we compare the calculated value of MPEL in fuel equivalents with the actual consumption of fuel resources for the needs of the national economy. These values ratio can serve as a standard for measuring and balancing the environmental and economic system. We authors have validated the described method on the example of the Sverdlovsk region, which is characterized by a high level of man’s impact. Calculations show that the actual consumption of fossil fuels in the region exceeds MPEL. Wat indicates an imbalance in the ecological and economic system and may lead to further deterioration of the environmental quality in the region. We proposed methodological approach and calculations can be used when developing strategic planning documents for a territory, including its energy strategy.